The Influence Of Self-Regulation And Social Support On Academic Procrastination Among Students - Riska Santi Safitri; Vabresty Hareni; Nur Shabrina Octarisa; Rilla Sovitriana (CV. Doki Course and Training, 2025)
This study investigates the influence of self-regulation and social support on academic procrastination among students at one of the private universities in Jakarta. Academic procrastination, defined as the intentional delay of academic tasks despite awareness of negative consequences, is a prevalent issue that undermines student performance, increases stress, and affects well-being. This quantitative research employed a census sampling method, involving 96 students from the Faculty of Education. Data were collected using validated psychometric scales: academic procrastination (14 items, α=0.833), self-regulation (19 items, α=0.839), and social support (18 items, α=0.946). Simple and multiple linear regression analyses, conducted with IBM SPSS Statistics 24, revealed significant results. Self-regulation exhibited a strong negative effect on academic procrastination (t=-7.189, p=0.000<0.05, β=-0.596), indicating that enhanced self-regulatory skills, such as goal-setting and time management, reduce procrastination tendencies. Social support also demonstrated a significant negative effect (t=-2.829, p=0.006<0.05, β=0.280), suggesting that encouragement from family and peers mitigates delay behaviors. Together, self-regulation and social support significantly predicted academic procrastination (F=25.629, p=0.000<0.05), explaining 35.5% of the variance. These findings highlight the critical roles of self-regulation and social support in addressing academic procrastination. Practically, the results advocate for interventions like time management workshops and peer support groups to foster academic productivity. This study contributes to educational psychology by offering evidence-based strategies to reduce procrastination, enhancing student success and well-being in higher education settings.